The Communication and Seeking Information of Mental Health Services among Students in Universitas Airlangga Indonesia - Widati, Sri; Zainuddin, Suria; Garg, Pooja; Nurmala, Ira; Nastiti, Rizma Dwi (Journal of Public Health and Pharmacy, 2026)
Introduction: For teenagers, mental health is a big problem during the COVID-19 pandemic and post pandemic. Only a few teenagers seek professional help for mental health problems. In the last 12 months, only 2.6% of youth with mental health problems used mental health facilities or counseling to deal with their emotional and behavioral problems. The purpose of study is to determine the effect of demographic characteristics, knowledge, attitudes, social support, ability to do self-efficacy, distance to health services and stigma on the intention and behavior of seeking mental health services among students at the Universitas Airlangga Indonesia. Methods: The research is a cross-sectional study using questionnaires distributed through google form. The participants are 324 Universitas Airlangga students. The data was analyzed by logistic regression to examine the effect of independent variables to dependents variables. Results: The results showed that the attitude of the respondents, the ability of the respondents in self-control and the intention as well as social support have significant influence on the behavior of students in seeking mental health services. Conclusion: Campus should provide full support to students in seeking mental health services by providing infrastructure and communication system, both physical and mental, such as counseling services with professionals.